Battling with words : a study of language, diversity and social inclusion in the Australian Department of Defence - Thomson, Elizabeth A. (Elizabeth Anne), 1961-; Australia. Department of Defence ([Canberra, Australian Capital Territory] : Department of Defence, 2014)
"The Australian Department of Defence is responsible for the security and defence of Australia - a diverse nation of multicultural and multilingual people. Yet, the demographic makeup of Defence does not reflect the demography of the Australian community which it serves. Compared to the wider community, Defence is an Anglo-Australian, male-dominated organisation. This profile is no longer sustainable particularly if the Australian community is to have trust and confidence in the organsiation and if future capability is to be enhanced. A major challenge for Defence is to create a workplace culture that shifts the institution away from an exclusive, homogeneous culture to an inclusive heterogeneous one. This report investigates the role language plays in perpetuating cultural norms and offers recommendations for changing language usage, arguing that unless the language practices of the institution change in concert with other social inclusion policy changes, it will be difficult for leadership to 'walk the talk' of change. It demonstrates how language and culture are inextricably linked. If Defence wants to increase diversity, then it needs to turn its attention to the role language plays formally and informally to both include and exclude so that it can create a Department of Defence characterised by the highest possible degree of sustainable diversity and social inclusion, and ultimately the greatest capability."--Back cover.
List of tables, figures and charts -- Preface -- Summary -- Recommendations -- chapter 1. Diversity and social inclusion -- chapter 2. Frameworks and methodologies -- chapter 3. Four cultures, one Department -- chapter 4. Values and icons to rally around -- chapter 5. Everyday talk and inclusion -- chapter 6. Towards social inclusion -- appendix A. Interview plan and prompt sheet -- appendix B. Annotated hero texts -- appendix C. Dining in night, a script of formal banter -- Acknowledgements -- References.
"DPS-JUL027-14"--Back cover.
Title from PDF title page.
Includes bibliographical references (pages 155-162)
Also available in print.
Viewed on March 13, 2020
Keywords: Australia. -- Department of Defence -- Officials and employees; Australia. -- Department of Defence; Diversity in the workplace -- Australia; Language and culture -- Australia; Language in the workplace -- Australia; Social integration -- Australia; Electronic books